2022
DOI: 10.3390/foods11233878
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and Protein Oxidation of Brown Rice and Selenium-Rich Brown Rice during Storage

Abstract: Selenium-rich rice has become one of the effective ways to increase people’s selenium intake. Selenium-containing proteins have higher antioxidant properties, which may lead to selenium-rich brown rice (Se-BR) having better storage stability than ordinary brown rice (BR). By measuring the peroxidation value, fatty acid value, carbonyl value and protein secondary structure, it was found that Se-BR had higher oxidation resistance stability than BR. The biological function of the differential proteins (DEPs) betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…These lipid peroxides also affect the rice by reducing the edible quality and nutritional value [ 86 ]. The lipid free radicals also results in intramolecular and intermolecular cross-linking with protein which seriously cause loss in the availability of different amino acids like phenylalanine, lysine, tryptophan, tyrosine and methionine [ 87 ]. Moreover, the lipid peroxidation has also been associated with off-flavor and off-odor of rice during the storage periods.…”
Section: Resultsmentioning
confidence: 99%
“…These lipid peroxides also affect the rice by reducing the edible quality and nutritional value [ 86 ]. The lipid free radicals also results in intramolecular and intermolecular cross-linking with protein which seriously cause loss in the availability of different amino acids like phenylalanine, lysine, tryptophan, tyrosine and methionine [ 87 ]. Moreover, the lipid peroxidation has also been associated with off-flavor and off-odor of rice during the storage periods.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins can form a firm mesh structure around the starch and limits the expansion and digestion of starch. Because of the oxidation of proteins leads to the increase in the content of carbonyl compounds in brown rice [27]. Liu et al [28] reported that the carbonyl values of brown rice gradually increased with the increase in storage time at 15 °C and 25 °C, reaching the maximum values of 5.20 and 8.31 meqkg-1 after 270 days, respectively.…”
Section: Influence On the Protein Of Brown Ricementioning
confidence: 99%
“…Most of the fa y acids in brown rice are unsaturated, and the double bonds within their molecular structure can be oxidized to generate some carbonyl compounds. Lipids in aged brown rice are hydrolyzed by lipase to produce glycerol and free fa y acids [27,32]. The fa y acid value is one of the most used and core indicators to reflect the freshness of brown rice.…”
Section: Influence On the Crude Fat Of Brown Ricementioning
confidence: 99%
See 1 more Smart Citation
“…Compared to fresh rice, the solubility of total starch and amylose decreased, resulting in a lower gelatinization temperature, greater hardness, and lower viscosity of the rice [5]. Moreover, the lipid oxidation increased the contents of free fatty acids and volatile carbonyl compounds, such as glutaraldehyde and hexanal, which reduced the palatability of the stored grain [6].…”
Section: Introductionmentioning
confidence: 99%